Limpopo River Basin Digital Twin Open Data Cube Catalog - Afham, Abdul; Silva, Paulo; Ghosh, Surajit; Kiala, Zolo; Retief, H.; Dickens, Chris; Garcia Andarcia, Mariangel (International Water Management Institute, 2024)
A Limpopo River Basin (LRB) Digital Twin, a significant technological innovation, is being developed to assist water managers to assess and manage the water resources of the basin in sustainable ways. At the core of this innovation, the LRB Digital Twin compiles and serves a variety of raster datasets with unique spatial and temporal resolutions tailored to the basin’s characteristics. These datasets include hydrological variables (e.g., precipitation), climate indicators (e.g., temperature), and land surface characteristics (e.g., vegetation cover, land use). Each data set compromises with advanced preprocessing, fusion, and calibration to ensure consistency, accuracy, and reliability, making it suitable for long-term analysis and immediate decision-making.